Effects of temperature and salinity on the growth of Alexandrium (Dinophyceae) isolates from the Salish Sea. Issue 2 (25th February 2016) - Bill, Brian D.; Moore, Stephanie K.; Hay, Levi R.; Anderson, Donald M.; Trainer, Vera L.
Abstract : Toxin‐producing blooms of dinoflagellates in the genus Alexandrium have plagued the inhabitants of the Salish Sea for centuries. Yet the environmental conditions that promote accelerated growth of this organism, a producer of paralytic shellfish toxins, is lacking. This study quantitatively determined the growth response of two Alexandrium isolates to a range of temperatures and salinities, factors that will strongly respond to future climate change scenarios. An empirical equation, derived from observed growth rates describing the temperature and salinity dependence of growth, was used to hindcast bloom risk. Hindcasting was achieved by comparing predicted growth rates, calculated from in situ temperature and salinity data from Quartermaster Harbor, with corresponding Alexandrium cell counts and shellfish toxin data. The greatest bloom risk, defined at μ >0.25 d −1, generally occurred from April through November annually; however, growth rates rarely fell below 0.10 d −1 . Except for a few occasions, Alexandrium cells were only observed during the periods of highest bloom risk and paralytic shellfish toxins above the regulatory limit always fell within the periods of predicted bloom occurrence. While acknowledging that Alexandrium growth rates are affected by other abiotic and biotic factors, such as grazing pressure and nutrient availability, the use of this empirical growth function to predict higher risk time frames for blooms and toxic shellfish within the Salish Sea provides the groundwork for a more comprehensive biological model of Alexandrium bloom dynamics in the region and will enhance our ability to forecast blooms in the Salish Sea under future climate change scenarios.